Incidence Trends of Lip, Oral Cavity, and Pharyngeal Cancers: Global Burden of Disease 1990–2017. (February 2020) - Du, M.; Nair, R.; Jamieson, L.; Liu, Z.; Bi, P.
The worldwide incidence trends of the lip, oral cavity, and pharyngeal cancers (LOCPs) need to be updated. This study aims to examine the temporal incidence trends of LOCPs from 1990 to 2017, using the latest Global Burden of Disease (GBD) study data to explore sex, age, and regional differences. GBD incidence data for LOCPs were driven by population cancer registries and were estimated from mortality data. Age-standardized incidence rates (ASIRs) were directly extracted from the 2017 GBD database to calculate the estimated annual percentage change (EAPC) over the study period. Incidence trends are mapped and compared separately by sex (females vs. males), age groups (15–49, 50–69, and 70+ y), regions (21 geographical and 5 sociodemographic regions), and countries. Among 678, 900 incident cases of LOCPs notified in 2017, more than half were lip and oral cavity cancers. From 1990 to 2017, the estimated global incidence for nasopharyngeal cancers decreased dramatically (EAPC = −1.52; 95% confidence interval [CI], –1.70 to −1.34), while the incidence for lip and oral cavity cancers (EAPC = 0.26; 95% CI, 0.16–0.37) and other pharyngeal cancers (EAPC = 0.62; 95% CI, 0.54–0.71) increased. Higher ASIRs were observed among males than females across all age groups. However, females had larger EAPC variation when compared to males. Population groups aged 15 to 49 y presented the lowest ASIRs, with larger values of EAPC than those aged 50 to 69 and 70+ y. While high-income countries had higher ASIRs with little EAPC variation, ASIRs varied across low/middle-income regions with larger EAPC variations. South Asia and East Asia had the highest ASIRs and EAPC for lip and oral cavity cancers, respectively. In conclusion, the global incidence of LOCPs has increased among females, those aged 15 to 49 y, and people from low/middle-income countries over the study period, excepting nasopharyngeal cancers, which had a decreasing worldwide trend.